The Relationship Between Anxiety and Psychosomatic Tendencies Among Students at SMA Negeri 3 Banda Aceh - Siregar, Muhammad Rizqi Rirwanda; Safrilsyah, Safrilsyah; Karjuniwati, Karjuniwati (Faculty of Psychology, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Excessive psychosomatic symptoms can disrupt an individual’s emotional state. One of the factors that influences psychosomatic tendencies is anxiety. This study aims to determine the relationship between anxiety and psychosomatic tendencies among students at SMA Negeri 3 Banda Aceh. The research employed a quantitative approach using a correlational method. The population in this study consisted of 1,066 students, with a sample of 258 students selected using the proportionate stratified random sampling technique. The instruments used were the Anxiety Scale and the Psychosomatic Tendency Scale. Data were analyzed using the Spearman’s rho correlation test, which showed a correlation coefficient of r = 0.458 with a significance value (p) = 0.000. These results indicate a highly significant positive relationship between anxiety and psychosomatic tendencies among students at SMA Negeri 3 Banda Aceh. This means that the higher the anxiety, the higher the psychosomatic tendencies, and conversely, the lower the anxiety, the lower the psychosomatic tendencies. Both anxiety and psychosomatic tendencies in this study were found to be within the moderate category.